Quizalofop tank mixtures for control the main paddy rice weeds occurring in Southern Brazil - Martins Chiapinotto, Diego; de Avila, Luis Antonio; Vianna Junkes, Gustavo; Schaedler, Carlos Eduardo; Camargo Aranha, Bianca; Rabaioli Camargo, Edinalvo (Revista Ceres, 2025)
Quizalofop-p-ethyl is used in ProvisiaTM rice for selecive grass weed control. In southern Brazil, other weeds occur, and an herbicide tank mix is needed to achieve a broad spectrum. This study aimed to evaluate the interaction of quizalofop-p-ethyl with other herbicides used to control the main paddy rice weeds occurring in Southern Brazil. Two greenhouse experiments were performed using Aeschynomene denticulata Rudd (jointvetches), Cyperus iria L. (rice flatsedge), Echinochloa crus-galli L. (barnyard grass), and Oryza spp. (weedy rice). The factorial arrangement to each species comprises: Factor A) Doses of quizalo-fop-p-ethyl (g ha-1): 0, 120, and 120 plus 120 (applied 14 days after the initial treatment - DAIT); Factor B) Tank mix partner: bentazon (960 g ha-1), florpyrauxifen-benzyl (30 g ha-1), quinclorac (375 g ha-1), saflufenacil (30 g ha-1), and control. At 42 DAIT, control and shoot dry weight (SDW) were evaluated. Colby’s method compared treatments using Tukey’s HSD and tank mix. No herbicide tank mix reduced or increased the variables evaluated compared to the herbicides applied alone, suggesting a neutral effect. Between the mixtures, in terms of spectrum of weed control, quizalofop-p-ethyl plus florpyrauxifen-benzyl was the best treatment, providing effective control or SDW reduction (≥ 90%) in all tested species.